Anti‐proliferative and Apoptotic Effects of Coordination Compounds of Zinc(II), Palladium(II), and Platinum(II) with Tridentate 4‐(6‐hydroxyphenyl)‐2, 6‐di(thiazol‐2‐yl)pyridine. Issue 13 (3rd April 2023) - Pekdemir, Fatih; Sengul, Abdurrahman; Akgun, Oguzhan; Ari, Ferda; Acar‐Selcuki, Nursel
Abstract: The mononuclear coordination compounds, [Zn(L)Cl2 ] (1 ), [Pd(L)Cl]Cl (2 ), and [Pt(L)Cl]Cl (3 ) (L) is a tridentate‐coordinated of 4‐(6‐hydroxyphenyl)‐2, 6‐di(thiazol‐2‐yl)pyridine) were synthesized and characterized by different spectroscopic methods (FTIR, MALDI‐TOF‐MS, 1 H NMR, 13 C NMR, and UV/Vis). By using density functional theory (DFT) and time‐dependent DFT (TD‐DFT) methods, the geometrical parameters, UV/Vis absorption spectra, and infrared vibrational frequencies for the investigated compounds were explored. Anticancer activities of these compounds were determined by SRB viability assay in human lung (A549 and H1299), prostate (LNCAP), colorectal (HT‐29), breast cancer (MDA‐MB‐231) and healthy bronchial (BEAS‐2B), breast (MCF‐10A), colon (CCD‐18Co), and prostate (WPMY‐1) epithelial cells. Caspase 3/7 activity, cleaved cytokeratin‐18, and PARP levels were measured to determine apoptosis in the metal compounds found to be effective. Among the compounds, 1 showed a selective inhibiting effect and induced apoptosis on the cancer cells, thus further analyses are needed to evaluate its antitumor/anticancer activity. Abstract : Pd(II), Pt(II) and Zn(II) coordination compounds of the 2, 2 ′ : 6 ′, 2 " ‐terpyridine (terpy)‐like ligand were synthesized and characterized. Anticancer activities of the compounds against various cancer cell lines were investigated. The Zn(II) compound has a growth‐suppressive effect and induces apoptosis in cancer cells was determined. Also, this compound was found to exhibit selective toxicity and not caused cell death.